2021
DOI: 10.1007/s00467-021-05107-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of urine biomarkers in children with IgA vasculitis nephritis

Abstract: Background Nephritis is a recognised complication of IgA vasculitis (IgAV, Henoch-Schönlein purpura) contributing to 1–2% of all chronic kidney disease (CKD) stage 5. Improved understanding may reduce irreversible damage in IgAV nephritis (IgAV-N). Objective The aim of this study was to perform a comprehensive systematic literature review to identify promising clinical and pre-clinical urine biomarkers in children with IgAV-N that could predict the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Among urinary biomarkers, IgA and IgM performed best in the study conducted by Pillebout et al ( 45 ). Recent systematic review of urine biomarkers in children with IgAVN showed that the most promising urinary biomarkers in predicting nephritis were kidney injury molecule-1 (KIM-1), monocyte chemotactic protein-1 (MCP-1), N-acetyl-β-glucosaminidase (NAG), and angiotensinogen (AGT) ( 71 ). However, none of them proved yet to be an established marker of disease.…”
Section: New Insights In the Diagnostics Of Igav With Special Emphasi...mentioning
confidence: 99%
“…Among urinary biomarkers, IgA and IgM performed best in the study conducted by Pillebout et al ( 45 ). Recent systematic review of urine biomarkers in children with IgAVN showed that the most promising urinary biomarkers in predicting nephritis were kidney injury molecule-1 (KIM-1), monocyte chemotactic protein-1 (MCP-1), N-acetyl-β-glucosaminidase (NAG), and angiotensinogen (AGT) ( 71 ). However, none of them proved yet to be an established marker of disease.…”
Section: New Insights In the Diagnostics Of Igav With Special Emphasi...mentioning
confidence: 99%
“…As biomarkers for IgA nephritis, a systematic literature review was performed to predict the presence of IgA nephritis or determine its severity [ 134 ]. In urine samples, kidney injury molecule-1 (KIM-1), monocyte chemotactic protein-1 (MCP-1), and N-acetyl-β-glucosaminidase (NAG) correlate with the disease severity of nephritis.…”
Section: Biomarkermentioning
confidence: 99%
“…IgAV is more frequent in childhood with a peak incidence around 4-6 years of age 2,4 . The disease usually presents with a palpable purpuric rash, gastrointestinal pain and bleeding, kidney involvement, arthralgia and/or arthritis [1][2][3][4] . Testicular inflammation (orchitis: 14% of male patients) is also seen, manifested by pain and swelling 5 .…”
mentioning
confidence: 99%
“…Immunoglobulin A (IgA) vasculitis (IgAV), classically known as Henoch-Schönlein purpura, is a type of non-thrombocytopenic small-vessel vasculitis and is the most frequent form of childhood systemic vasculitis (annual incidence: 3-26.7 per 100,000, depending on the country) 1 - 3 . IgAV is more frequent in childhood with a peak incidence around 4-6 years of age 2 , 4 . The disease usually presents with a palpable purpuric rash, gastrointestinal pain and bleeding, kidney involvement, arthralgia and/or arthritis 1 - 4 .Testicular inflammation (orchitis: 14% of male patients) is also seen, manifested by pain and swelling 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation